2018
DOI: 10.1186/s12884-018-2017-5
|View full text |Cite
|
Sign up to set email alerts
|

Logistical, cultural, and structural barriers to immediate neonatal care and neonatal resuscitation in Bihar, India

Abstract: BackgroundIn India, the neonatal mortality rate is nearly double the Sustainable Development Goal target with more than half of neonatal deaths occurring in only four states, one of which is Bihar. Evaluations of immediate neonatal care and neonatal resuscitation skills in Bihar have demonstrated a need for significant improvement. However, barriers to evidence based practices in clinical care remain incompletely characterized.MethodsTo better understand such barriers, semi-structured interviews were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 24 publications
1
41
0
1
Order By: Relevance
“…Comprehensive literature review was conducted to find variables or factors which affect maternal health referral system. Several factors were included in this instrument such as age, geographical access, indication for referral, referral staff, initial procedure/treatment prior referral, communication, transportation vehicle, insurance coverage, and distance for referral [4,5,6,7,8] Below was an instrument that we have already formulated entitled Phyo Referral Score (PRS) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive literature review was conducted to find variables or factors which affect maternal health referral system. Several factors were included in this instrument such as age, geographical access, indication for referral, referral staff, initial procedure/treatment prior referral, communication, transportation vehicle, insurance coverage, and distance for referral [4,5,6,7,8] Below was an instrument that we have already formulated entitled Phyo Referral Score (PRS) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…There are several important factors affecting the quality of referral system such as staff, protocols, transportation, communication, and geographical access/distance [4,5,6,7] that need to be concerned by the stakeholders which involved in the maternal and child health program. By evaluating the quality of referrals it can be found which factors that were not working optimally and could be considered for maternal and perinatal audit.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason was the lack of recognition that a large proportion of maternal morbidity and mortality occurs in the postpartum period 39 . Another study revealed that cultural barriers include cultural norms such as preference over male infant and traditional clinical practices delays maternal care seeking among Indian women 38 .…”
Section: E Leadership and Governancementioning
confidence: 99%
“…Perceived low-quality services are barriers for delivery and postpartum care access for rural Indian and Nepal women 20,39,44,45 . Financial constrains due to poverty was detected as an overarching structural barrier for access 38,39,46 .…”
Section: E Leadership and Governancementioning
confidence: 99%
See 1 more Smart Citation